An ecological model for digital platforms maintenance and evolution - ROCCHI, Paolo (Institutional Knowledge at Singapore Management University, 2014)
The maintenance of software products has been studied extensively in both software engineering and management information systems. Such studies are mainly focused on the activities that take place prior to starting the maintenance phase. Their contribution is either related to the improvement of software quality or to validating contingency models for reducing maintenance efforts. The continuous maintenance philosophy suggests to shift the attention within the maintenance phase for better coping with the evolutionary trajectories of digital platforms. In this paper, we examine the maintenance process of a digital platform from the perspective of the software vendor. Based on our empirical observations, we derive an interesting statistical relationship that has strong theoretical and practical implications in the study of software defects.